Preference Rattus Tiomanicus Mill. against Various Rodenticide Formula Aroma and Taste in Storage Container - Natawigena, Wahyu Daradjat; Bari, Ichsan Nurul; Subakti-Putri, Syifa Nabilah; Yulia, Endah; Nurmahmudah, Sarah (Journal of Ecohumanism, 2025)
Rattus tiomanicus (Malayan field rat) attacks oil palm trees, and rodenticides without protective containers (bait stations) become stale due to rain and sunlight exposure. This study aims to identify a rodenticide preferred by R. tiomanicus using suitable bait stations. A multiple-choice test with 15 treatments and 3 replications was conducted, using bromadiolone, supplemented with peanut butter, cricket flour, cheese, salted fish, cocoa powder, and desiccated coconut powder. Bait station materials tested were Ivory paper (210 gsm), Duplex paper (230 gsm), and Wax paper (220 gsm). Data were analyzed using a Completely Randomized Factorial Design (CRFD). Results showed a significant influence of formula and bait station material on rodenticide consumption by R. tiomanicus, with a slight correlation between formula treatments and bait station materials. The best formula was a combination of salted fish, chocolate, peanut butter, and desiccated coconut powder in a Wax paper bait station, with a preference score 10.82 times higher than control. All bait station materials maintained the quality of the rodenticide during the treatment. In conclusion, the study identified that a rodenticide with salted fish, chocolate, peanuts, and desiccated coconut powder in a wax paper bait station effectively controls R. tiomanicus for use at oil palm plantations.